Directive Illocutionary Act Found in The Commuter Film - Nurcahyadi, Yulian Kristalia; Candra, Komang Dian Puspita; Maharani, Putu Devi (LPPM Universitas Dhyana Pura, 2024)
The study aimed to analyze the type of directive illocutionary act spoken by all characters in the commuter film. The theory of Searle and Vanderveken (1985) on the type of directive illocutionary act is used in analyzing data findings. Halliday's theory (1985) of context of situation also supports the analysis in this study. Data were analyzed by using descriptive qualitative method.Â There are 91 utterance of directive illocutionary act found in the movie. The most dominant type is commanding act with 44 data (49%) occurrences followed by asking act with 30 data (33%) occurrences. The last type is ordering act with 17 data (18%) occurrences. The movie that used as the data source is a thriller-themed movie about the main actor who works on a mission given by someone. Thus, this movie contained many types of command, ask and order act.